Global feminist autoethnographies during COVID-19 displacements and disruptions - Heath, Melanie F.; Darkwah, Akosua Keseboa; Beoku-Betts, Josephine A. 1951-; Purkayastha, Bandana 1956- (Routledge, Taylor & Francis Group, 2022)
"Global Feminist Autoethnographies uses feminist methods to reflect on our experiences of precarities as tenured faculty, faculty on temporary contracts, and graduate students during COVID-19. This book bears witness to the displacements, disruptions, and distress experienced by women in different locations in academia. The authors document their experiences arising within academia and beyond it, gathering stories from across the globe-Australia, Canada, Ghana, Finland, India, Norway, South Africa, United Kingdom, United States along with transnational engagements with Bolivia, Iran, Nepal, and Taiwan. In an era where the older rules about work and family related to our survival, wellbeing, and dignity are rapidly being transformed, this book shows that distress and traumas are emerging across the divides between the global North and South, depending on the intersecting structures that have affected each of us. It documents our distress and trauma and how we have worked to lift each other up amidst severe precarities. A global co-written project, this book shows how we are moving to decolonize our scholarship. It will be of interest to an interdisciplinary array of scholars in the areas of intersectionality, gender, family, race, sexuality, migration, and global and transnational sociology
Includes bibliographical references and index
Keywords: Pandemie; COVID-19; Sozialer Wandel; Frau; Feminists / History / 21st century; Women scholars / History / 21st century; Feminist theory / History / 21st century; COVID-19 (Disease) / Social aspects; Social change / History / 21st century; Féministes / Histoire / 21e siècle; Savantes / Histoire / 21e siècle; Théorie féministe / Histoire / 21e siècle; COVID-19 / Aspect social; Feminist theory; Feminists; Social change; Women scholars; 2000-2099; History